THE EFFECT OF USING MIND MAPPING TECHNIQUE ON WRITING PROCEDURE TEXT OF ELEVENTH GRADE STUDENTS OF SMA NEGERI 1 TANJUNG PURA IN ACADEMIC YEAR 2016/2017 - Syafriza Ulfa; Ayu Indari (Jurnal Serunai Bahasa Inggris, 2020)
This study deals with the effect of using mind mapping technique on students’ writing procedure text. The objective of this study was to find out if there was a significant effect of mind mapping technique on writing procedure text. It was conducted by using experimental research. The population of this study was the eleventh-grade students of SMA Negeri 1 Tanjung Pura which consists of six parallel classes. Two classes were taken as the sample of this research, XI MIA-1 and XI MIA-2. The class of XI MIA-1 was an experimental group and class XI MIA-2 was a control group. The experimental group was taught by mind mapping technique, otherwise the control group was taught by using lecturing technique. The instrument for collecting the data was writing test. The data were analyzed by using t-test formula. It was found that t-observed (5.98) higher than t-table (1.99). It means that there was a significant effect on students’ writing procedure text at SMA Negeri 1 Tanjung Pura by using mind mapping technique.